The Mediating Role of Employee Motivation in The Relationship Between Budget Participation and Budgetary Slack - Fajra Octrina; May Swastawati (Universitas Mercu Buana, 2023)
Objectives: A budget is a plan expressed in the company's financial measures as a guideline for work in a certain period. Budgeting involves many parties starting from the top and bottom levels, making it vulnerable to budgetary slack. The purpose of this study is to examine employee motivation at the corporate offices of PT ASDP Indonesia Ferry (Persero) in order to ascertain the impact of budgetary participation on the occurrence of budgetary slack.Methodology: This study used quantitative research by conducting surveys through questionnaires. The respondents in this study were 211 employees of PT ASDP Indonesia Ferry (Persero) head office and were analyzed using path analysis.Finding: The findings indicated that when employees at PT ASDP Indonesia Ferry (Persero) head office are directly involved in budgeting, it has a noteworthy and favorable impact on their motivation and the occurrence of budgetary slack. Employee motivation has a direct and significant positive effect on budgetary slacks at PT ASDP Indonesia Ferry (Persero). Additionally, employee motivation at the PT ASDP Indonesia Ferry (Persero) headquarters can mediate the impact of budget participation on budgetary slack.Conclusion: This study highlights the significance of employee involvement in budgeting for enhancing motivation and reducing budgetary slacks. It underscores the need for balanced budget participation to maintain control and suggests that employee motivation acts as a vital mediator in this relationship, offering valuable insights for optimizing budget processes and fostering workforce efficiency.